High‐resolution scanning tunneling and atomic force microscopy of stereochemically resolved dibenzo[a, h]thianthrene molecules. Issue 11 (9th August 2013) - Pavliček, Niko; Herranz‐Lancho, Coral; Fleury, Benoit; Neu, Mathias; Niedenführ, Judith; Ruben, Mario; Repp, Jascha; Frauenheim, Thomas; Niehaus, Thomas; Repp, Jascha; Richter, Klaus; Weber, Heiko
<x xml:space="preserve">Abstract</x> Recently, we reported on the bistable configurational switching of dibenzo[a, h]thianthrene (DBTH) molecules adsorbed on NaCl using combined low‐temperature scanning tunneling and atomic force microscopy (STM/AFM). Here, we discuss the intra‐molecular contrast in AFM images of the molecules as a function of the tip–molecule distance. Our experiments show that ridges in the frequency shift do not necessarily correlate with chemical bonds in this case of a non‐planar molecule. To explain this finding we compare images acquired at different tip–molecule distances to the calculated electron density of the molecules obtained from density functional theory calculations (DFT). In addition, we analyze the probability of finding different configurations after adsorption onto the surface.<inline-graphic xlink:href="ark:/27927/pgg3v1bqs56" content-type="pssb201349229-gra-0001" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> DBTH molecules in two configurations probed by a CO‐functionalized tip. Insets show AFM (left) and STM (right) images of a U molecule.